2005
DOI: 10.1016/j.urology.2004.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase-10 in human bladder transitional cell carcinoma

Abstract: 'Expression of matrix metalloproteinase-10 in human bladder transitional cell carcinoma.', Urology., 65 (4).pp. 815-820.Further information on publisher's website:http://dx.doi.org/10. 1016/j.urology.2004.11.016 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Urology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
(40 reference statements)
3
21
0
Order By: Relevance
“…To address whether elevated CYP1A1 mRNA is reflective of CYP1A1 protein, immunohistochemical analyses of human bladder TCC TMAs were conducted, an approach previously shown with TCC to be highly representative of whole histologic sections (22,26). Expression of CYP1A1 was detected in all pathologic stages of TCC, with a correlation between increasing tumor stage and CYP1A1 expression (Supplementary Table S1.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address whether elevated CYP1A1 mRNA is reflective of CYP1A1 protein, immunohistochemical analyses of human bladder TCC TMAs were conducted, an approach previously shown with TCC to be highly representative of whole histologic sections (22,26). Expression of CYP1A1 was detected in all pathologic stages of TCC, with a correlation between increasing tumor stage and CYP1A1 expression (Supplementary Table S1.1).…”
Section: Resultsmentioning
confidence: 99%
“…CYP1A1 protein expression was assessed by immunohistochemistry in a TMA of human bladder TCC, as previously described (22). The specific protocol for CYP1A1 expression is shown in Supplementary Methods.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This observation is in agreement with several published studies. MMP-1 and MMP-10 mRNA levels have been reported to be significantly higher in bladder cancers compared with normal urothelial tissues (43,44), and MMP-1 and pro-MMP-10 immunoreactivity is evidently stronger in tumor cells of both superficial and muscle-invasive bladder cancers (45,46). In addition, patients with bladder cancer with an increased urinary MMP-1 protein level are more likely to have an aggressive tumor of advanced stage and grade (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MMP-7 plays an important role in the metastases of endometrial, gastrointestinal carcinomas, colorectal cancer, and lung cancer (Shiomi et al, 2003;Safranek et al, 2009;Shi et al, 2010). It has been demonstrated that MMP-10 was overexpressed in several human tumors of epithelial origin, including gastric cancer, esophageal carcinoma, skin carcinoma, and bladder transitional cell carcinoma determined using the immunohistochemical staining or microarray techniques (Kerkela et al, 2001;Mathew et al, 2002;Seargent et al, 2005;Aung et al, 2006). There is no published study on the detection of MMP-7 and MMP-10 in PE.…”
Section: Introductionmentioning
confidence: 99%